Pengaruh Mirza Basyiruddin Mahmud Ahmad dalam tafsiran Al-Quran dan penyebaran ajaran Qadiani di Sumatera, Indonesia (Influence of Mirza Basyiruddin Mahmud Ahmad in Quranic Interpretation and Spreading of Qadiani Teaching in Sumatera, Indonesia) - Abdullah, Mustaffa; Ishak, Andi Putra; Ali, Abdul Karim (Dept of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, Malaysia, 2019)
Mirza Basyiruddin Mahmud Ahmad is the second caliph of Jemaat Ahmadiyyah Qadiani, who tried to develop his thoughts in understanding the Qur’an to the whole world including the Island of Sumatra. Basyiruddin’s thoughts have caused controversy while believing the death of Jesus and prophethood of Mirza Ghulam Ahmad. This article aims to examine the influence of these ideas in Sumatra. Regions that were the focus of the study are Aceh, West Sumatra and North Sumatra. This study used the method of library research and interviews. The results of this study found that Basyiruddin’s thoughts were opposed by public, prominent scholars and government, because of contradiction to the fundamentals of Islamic religion. Therefore, these thoughts did not have a significant effect to the whole Sumatra. © 2019, Academy of Islamic Studies, Dept of Islamic History and Civilization, University of Malaya. All rights reserved.